I.iii.5. Miscellaneous correspondence of John Pitt Kennedy concerning agricultural schools - Kennedy, John Pitt, 1796-1879; Ireland. Education Commission; Board of Education (1836)
Correspondence of John Pitt Kennedy with various individuals/organisations concerning the agricultural schools at Loughash and Cloghan, as well as other national education issues. Correspondents include an unidentified member of the Spring-Rice family, members of the Education Commission, Thomas F. Kelly (secretary to the Board of Education), and John Anderson Coler(?).
Keywords: Loughash National and Agricultural School; Cloghan Agricultural School; Agricultural laborers -- Education -- Ireland -- 19th century